Uncovering the potential of evaluative conditioning in shaping attitudes toward sustainable product packaging - Leeuwis, Nikki; van Bommel, Tom; Tsakiris, Manos; Alimardani, Maryam (Frontiers in Psychology, 2024)
The necessity to promote pro-environmental behavior change in individuals and society is increasingly evident. This study aimed to investigate the effect of evaluative conditioning on consumers' perception of product packaging. We first produced two stimulus sets: one including images of supermarket products with different packaging and the other containing affective images of healthy nature (positive) and climate change impact (negative). These images were then paired in an evaluative conditioning experiment where respondents were informed about the impact of product packaging. We found an effect of conditioning depending on the initial sustainability perception that participants had toward product packaging. Pairing products for which participants were uncertain about their sustainability with negative or positive affective images had a significant effect on the sustainable associations of the consumers in a negative or positive direction respectively. However, the impact of conditioning on products that clearly had (un)sustainable packaging was not that strong. These results provide new tools and evidence to further investigate the power of evaluative conditioning in pro-environmental attitude and behavior change.